ANALISIS RESPON SISWA TERHADAP PENGGUNAAN MEDIA MOBILE LEARNING BERBASIS ANDROID PADA MATERI MOMENTUM DAN IMPULS (UPEJ Unnes Physics Education Journal, 2023)
This research aims to describe students’ response about android based mobile learning media on the topic of momentum and impulse. This research is descriptive research. The response questionnaire given to students consist of 5 aspect. The result of this study indicated that using android based mobile learning media on the topic momentum and impulse have average response score of 74,45%. With this score, the students’ response is in good criteria. Based on to the result, it can concluded that the use of android based mobile learning media on the topic momentum and impulse have a good response.